2021
DOI: 10.1101/2021.02.18.21251504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efferocytosis of SARS-CoV-2-infected dying cells impairs macrophage anti-inflammatory functions and clearance of apoptotic cells

Abstract: COVID-19 is a disease of dysfunctional immune responses, but the mechanisms triggering immunopathogenesis are not established. The functional plasticity of macrophages allows this cell type to promote pathogen elimination and inflammation or suppress inflammation and promote tissue remodeling and injury repair. During an infection, the clearance of dead and dying cells, a process named efferocytosis, can modulate the interplay between these contrasting functions. Here, we show that engulfment of SARS-CoV2-infe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…SP-D and SP-A binding to alveolar macrophages during inflammation occurs via their C-lectin domain and subsequent binding to the CRT/CD91 receptor complex via their collagenous tail region ( 88 , 109 ). Enhancement of apoptotic cell clearance during SARS-CoV-2 infection is paramount, especially when it has been shown that a dysfunctional efferocytosis in SARS-CoV-2-infected cell corpses suppresses macrophage anti-inflammation and efficient tissue repair allowing hyperinflammation and extensive tissue damage linked with COVID-19 ( 110 ).…”
Section: Surfactant Proteins Mannose-binding Lectin Complement 1q and The Coronavirusmentioning
confidence: 99%
See 2 more Smart Citations
“…SP-D and SP-A binding to alveolar macrophages during inflammation occurs via their C-lectin domain and subsequent binding to the CRT/CD91 receptor complex via their collagenous tail region ( 88 , 109 ). Enhancement of apoptotic cell clearance during SARS-CoV-2 infection is paramount, especially when it has been shown that a dysfunctional efferocytosis in SARS-CoV-2-infected cell corpses suppresses macrophage anti-inflammation and efficient tissue repair allowing hyperinflammation and extensive tissue damage linked with COVID-19 ( 110 ).…”
Section: Surfactant Proteins Mannose-binding Lectin Complement 1q and The Coronavirusmentioning
confidence: 99%
“…In a normal environment, SP-A and SP-D fulfil an anti-inflammatory role mediated by the binding of their C-lectin domain to the SIRPa receptor. During acute inflammation of the lungs, a deficient apoptotic cell clearance is overcome by the recruitment of mononuclear phagocytes and following the binding of foreign particles (viruses or apoptotic bodies) alveolar macrophages initiate inflammation and host defense reactions (88,109). SP-D and SP-A binding to alveolar macrophages during inflammation occurs via their C-lectin domain and subsequent binding to the CRT/CD91 receptor complex via their collagenous tail region (88,109).…”
Section: Surfactant Proteins Mannose-binding Lectin Complement 1q and The Coronavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates possible defects in clearance of dead and dying immune cells as damaging players for chronic inflammation and poor health during infection and post-COVID phase. Indeed, recent research showed a decrease in efferocytic receptors including the scavenger receptors CD36, SRA-I, αVβ5 integrin, TIM4, MERTK associated with impaired efferocytosis by macrophages in severe COVID-19 patients [160]. This suppresses macrophage anti-inflammatory and tissue repair programmes leading to high pro-inflammatory responses and damage, though further understanding of clearance mechanisms with a special focus on lytic death remnants is warranted for therapeutic applications.…”
Section: Altered Neutrophil Clearance Associated Pathologies and Therapeutic Approachesmentioning
confidence: 99%
“…COVID-19 infection has been shown to hamper the proper function of alveolar macrophages, although the mechanism remains vague. Thus, the inadequate clearance of apoptotic cells generated due to the SARS-CoV-2 infection contributes to COVID-19-associated autoimmune disorders [13] . Thus, the clearance of apoptotic bodies by boosting efferocytosis in SARS-CoV-2-infected tissues can play an important role in the management of COVID-19 pathology by preventing inflammatory responses, such as, a ‘cytokine storm’ [14] .…”
Section: Introductionmentioning
confidence: 99%